Society Centered: Marxist Approach, dari Eksploitasi Hingga Alienasi Pekerja - Muhamad Imron; Niki Puspita Sari (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
Exploitation of workers in the largest manufacturing industry in China is still ongoing. Arguing that high market demand makes factories raise the target of production of goods to ignore the interests of the workers. At the same time workers experience a severe depression because their various needs were eliminated by the greed of corporations that are guided by the ideology of capitalism. The relationship formed between the owner of the means and means of production with the owner of power is only based on economic determinants. The dominant group will emerge and it tends to impose rules, values ??and norms that it believes on the subordinate / powerless (subordinate) group in order to maintain the social structure that they deem beneficial to the group. This study wanted to find out about how the practice of worker exploitation from the standpoint of Karl Marx's theory. This study aims to uncover the practices that take place in the exploitation of workers at Foxconn companies. The approach used in this study is qualitative wrapped with a critical paradigm. And until now, exploitation of workers is still ongoing. Through the ideology of capitalism adopted, the corporation continues to practice exploitation, subordination to alienation of workers. Another thing that is no less important, the practice involves the state.